The media and the configuration of "Mental Maps": Their relation to institutional homogenization among university students and disciplina identities - Aparicio, Miriam Teresita (2013)
This study tests some hypotheses included in the psycho-socio-communicational paradigm, which emphasizes the long term cognitive effects of the media and the role of the psychosocial subject as recipient: the hypothesis of "agenda-setting" (Mc- Combs & Shaw, 1976). The four main objectives were: to elucidate the cognitive effects of the media in university graduates; to detect levels of manipulation and homogenization of their "mental maps"; to ascertain the personality factors that condition differential receptivity ("Filtering" of the news) (151 variables); to determine the degree of impact and incidence of the press in the public's mental patterns and in the university identities. The sample was made up of (N=516) graduates from Cuyo University (Argentina). Quanti-qualitative techniques were complemented: semi-structured survey and interviews). The incidence of psychology and education in the differential construction of "cognitive maps" was confirmed as well as the stronger incidence of the press as regards the impact caused by news and the mental homogenization.